2″‐4″ diameter GaN‐on‐sapphire substrates free of wafer bow at all temperatures. Issue 3 (5th March 2014) - Preble, Edward A.; Leach, Jacob H.; Metzger, Robert; Shishkin, Eugene; Udwary, Kevin A.
Abstract: A heteroepitaxial GaN‐on‐sapphire template growth strategy is presented that eliminates wafer bow in the final structure at both room temperature and at high crystal growth temperatures. The technology is demonstrated here on 2″ and 4″ substrate sizes with GaN epitaxy thicknesses up to 150 µm with a sub‐nm, epi‐ready, final surface roughness. Wafer bow vs. temperature measurements for (a) 15 µm of GaN on 4″ 650 µm thick sapphire showing 280 µm bow shift, (b) 10 µm GaN film on 2″ 430µm thick sapphire showing 120 µm bow shift, and (c) and (d), 15 µm of FLAAT GaN on 2″ and 4″ sapphire, respectively, each showing less than 30 µm of bow shift. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)